Melih Cevdet Anday’s “Dead Want to Talk” in Terms of the Playwriting Tendencies of “The Theater of the Absurd” - Simay Yılmaz (Konservatoryum)
Melih Cevdet Anday, one of the foremost playwrights in modern Turkish theater, has authored plays that exemplify the influence of “The Theater of the Absurd”. This article aims to explore the presence of absurdist tendencies within one of his works, "Dead Want to Talk". With this objective, the article has assessed the playwriting tendencies of “The Theater of the Absurd” and evaluated Anday’s play within this framework.It has been observed that the plot centers on the theme -the absurdity of human portraying passengers on a ferry who talk without taking action. Modern individualism and lack of communication are layers of thought, conveyed effectively through the use of self-centered monologues instead of meaningful dialogues. Symbolism plays a crucial role, with characters as anonymous figures lacking depth or development, representing various human portraits or traits. The vagueness in time and setting allows the plot to embrace ‘anytime’ / ‘anyplace’ where the modern individual exists. Additionally, the use of humor enables readers to engage with the critical perspective. In conclusion, Anday’s play exemplifies the influence of the playwriting tendencies of “The Theater of the Absurd” to a significant extent, thus serves as a notable example of the absurdist influence in modern Turkish Theater.